Programas públicos de geração de emprego para jovens e segregação espacial - Dener Antonio Chaves; Antonio Carvalho Neto (Ciências Sociais Unisinos)
This article analyses a particular public policy with a view to its spatial impact. Our assumption is that the government, when planning a focused public policy, does not take into consideration the spatial segregation of certain social groups. Since the increase of unemployment is a critical social problem, a factor that generates exclusion and segregation, and the category of young people exhibits the highest unemployment rate among the Economically Active Population, we observe the changes in the patterns of insertion of young people in the labor market and the negative consequences of these changes. Emphasis is given to the public policies that create jobs and sources of income, specially those focused on youth. Maps of Areas of Demographic Expansion of certain municipalities were used to check the possibilities of these programs to reach the neediest target group The article concludes that the social programs discussed may not reach the target groups that are often geographically segregated